Donitz and the wolf packs - Edwards, Bernard (Pen & Sword Maritime, 2014)
On 17 September 1942 Admiral Karl Donitz, C-in-C U-boats, issued the following directive: To all Commanders--'All attempts to rescue members of ships sunk, therefore also fishing out swimmers and putting them into lifeboats, righting capsized lifeboats, handing out provisions and water, have to cease. This book faithfully records the progress of the Battle of the Atlantic, which began within hours of the declaration of war on 3 September 1939 and continued without let-up until the last torpedo was fired on the night of 7 May 1945, just one hour before Germany surrendered.